Bone fracture healing within a continuum bone remodelling framework - Schmidt, Ina; Albert, Jacob; Ritthaler, Marina; Papastavrou, Areti; Steinmann, Paul (Computer Methods in Biomechanics and Biomedical Engineering, 2021)
Bone fracture healing is a complex process which is still under research. Computer-aided patient-specific prediction of bone development, fracture risk, prevention and treatment approaches promises a significant milestone in clinical practice. With this long-term goal in mind, a novel model is presented and examined in this work in the context of continuum bone remodelling. Therein, a clear distinction is made between external mechanical stimulation and the biological healing process of an injured bone tissue. The model is implemented within a finite element framework and investigated for the example of a fractured proximal femur head. The results show promising perspectives for further application. Besides, the model offers the possibility of easily integrating other factors like age-dependency and the availability of nutrition. For the future, further studies with large clinical datasets are essential for validation.
CRIS-Team Scopus Importer:2021-11-12
Keywords: bone fracture; Bone remodelling; femur head; finite element method; healing

Improved Motion Plane Adaptive 360-Degree Video Compression Using Affine Motion Models - Ritthaler, Marina; Regensky, Andy; Kaup, André (ICASSP 2025 - 2025 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2025)